Evidence based library and information practice: what's in it for you?. (21st May 2013) - Wilson, Virginia; Grant, Maria J.
Abstract With its roots in evidence‐based medicine, Evidence Based Library and Information Practice emerged 15 years ago and, with health librarians leading the way, has since been adopted by librarians and libraries in all sectors. EBLIP is an iterative process that may see you undertaking your own research although most likely, it will see you integrate your experience as a library and information professionals with research evidence generated both within and without the library science sector. As a library and information worker, you can use the Evidence Based Library and Information Practice process to help inform your decision‐making, streamline services and identify ways forward to fit your personal context.